Proceedings of the 2016 Conference on User Modeling Adaptation and Personalization 2016
DOI: 10.1145/2930238.2930241
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Users' Attitudes toward Smart Devices

Abstract: This paper presents a study to determine users' attitudes toward smart devices. We conducted a web survey to elicit users' ratings for devices and combinations of tasks and devices; the results of this survey led to the development of a Recommender System (RS ) for smart devices for particular tasks. We investigated user-and item-based Collaborative Filters, and compared their performance with that of global and demographic RS baselines. We then developed a technique based on Principal Components Analysis to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…H2 was rejected because elder people did not perceive Sony AIBO as a companion and younger generations were not more interested in the technology side of these robots. This result is similar to [24] in which Australian participants over 50 years disliked the robotic pets, younger Italian generations had more positive feelings towards robots in [26] and Ezer reached the same conclusion in [25] with American citizens, the acceptance was higher among younger adults in pre-adoption phase (without firsthand experience with robots). However, two studies [15,20] found the opposite in the Japanese society.…”
Section: Agesupporting
confidence: 77%
See 3 more Smart Citations
“…H2 was rejected because elder people did not perceive Sony AIBO as a companion and younger generations were not more interested in the technology side of these robots. This result is similar to [24] in which Australian participants over 50 years disliked the robotic pets, younger Italian generations had more positive feelings towards robots in [26] and Ezer reached the same conclusion in [25] with American citizens, the acceptance was higher among younger adults in pre-adoption phase (without firsthand experience with robots). However, two studies [15,20] found the opposite in the Japanese society.…”
Section: Agesupporting
confidence: 77%
“…The questionnaire was filled by 57 males and 19 females, since two participants did not reveal their gender, with a ratio 73%/24%, similar to the reported 69%/31% gender ratio of AIBO owners in [28] and another on-line AIBO questionnaire with 64%/36% in [1]. Although there was no question about the income and the wealth of the participants, the authors can explain this rate with the possible higher interest of the men in gadgets and they can afford more to buy expensive robots [16,24]. The technical enthusiasm was also reflected in the professions because most owners were engineers, software developers or technicians (27% for Tech in Fig.…”
Section: Questionnairementioning
confidence: 59%
See 2 more Smart Citations
“…Root mean square error (RMSE) (Zhan et al, 2016) was used to validate these eight models. RMSE can reflect the precision of models.…”
Section: Prediction Resultsmentioning
confidence: 99%